상백피(桑白皮) 메탄올 추출물 전처치가 일과성 허혈에 의한 생쥐의 뇌 손상에 미치는 영향 - 정병우; Byung-woo Chung; 임재유; Jae-yu Lim; 이세은; Se-eun Lee; 이병호; Byoungho Lee; 임세현; Sehyun Lim; 임지연; Chiyeon Lim; et al. (大韓本草學會誌, 2017)
Objectives : Mori Radicis Cortex (MRC), the root epidermis of Morus alba L., has been traditionally used to treat lung-related diseases in Korean Medicine. The common of MRC is Mulberry bark Morus bark, and it`s pharmaceutical properties and taste are known as sweet and cold, and it promotes urination and reduce edema by reducing heat from the lungs and soothe asthma. In the present study, anti-apoptotic mechanism of MRC in middle cerebral artery occlusion (MCAO) model in mice. Methods : Two-hundred grams of MRC was extracted with methanol at room temperature for 5 days, and this was repeated one time. After filtration, the methanol was removed using vacuum evaporator, then stored at -20℃ until use. C57BL/6 male mice were housed in an environment with controlled humidity, temperature, and light cycle. In order to determine beneficial effects of MRC on ischemia induced brain damage, infarct volume, neurological deficit scores, activities of several apoptosis-related proteins such as caspase-8, -9, Bcl-xL in MCAO-induced brains of mice were analyzed. Mice in MRC-treated groups were orally administered 30, 100, or 300 mg/kg of body weight for three consecutive days before commencing the MCAO procedure. Results : Pre-treatment of MRC significantly reduced infarct volume in MCAO subjected mice applied with 300 ㎎/ ㎏ of MRC methanol extract, and MRC effectively inhibited Bcl-xL reduction and caspase-9 activation caused by MCAO-induced brain damage. Conclusions : MRC showed neuro-protective effects by regulating apoptosis-related protein signals, and it can be a potential candidate for the therapy of ischemia-induced brain damage.